The limits of refusal: An ethical review of solid organ transplantation and vaccine hesitancy - Kates, Olivia S.; Stohs, Erica J.; Pergam, Steven A.; Rakita, Robert M.; Michaels, Marian G.; Wolfe, Cameron R.; Danziger‐Isakov, Lara; Ison, Michael G.; Blumberg, Emily A.; Razonable, Raymund R.; Gordon, Elisa J.; Diekema, Douglas S. (American journal of transplantation, 2021)
Patients pursuing solid organ transplantation are encouraged to receive many vaccines on an accelerated timeline. Vaccination prior to transplantation offers the best chance of developing immunity and may expand the pool of donor organs that candidates can accept without needing posttransplant therapy. Furthermore, transplant recipients are at greater risk for acquiring vaccine‐preventable illnesses or succumbing to severe sequelae of such illnesses. However, a rising rate of vaccine refusal has challenged transplant centers to address the phenomenon of vaccine hesitancy. Transplant centers may need to consider adopting a policy of denial of solid organ transplantation on the basis of vaccine refusal for non‐medical reasons (i.e., philosophical or religious objections or personal beliefs that vaccines are unnecessary or unsafe). Arguments supporting such a policy are motivated by utility, stewardship, and beneficence. Arguments opposing such a policy emphasize justice and respect for persons, and seek to avoid worsening inequities or medical coercion. This paper examines these arguments and situates them within the special cases of pediatric transplantation, emergent transplantation, and living donation. Ultimately, a uniform national policy addressing vaccine refusal among transplant candidates is needed to resolve this ethical dilemma and establish a consistent, fair, and standard approach to vaccine refusal in transplantation. The authors summarize ethical arguments both in favor of and against mandating compliance with routine vaccination for solid organ transplant candidates during the waitlisting process.